(untitled) - Larman, Craig (New Jersey, 1997)
Guides students through each step of requirements, analysis, design, and coding. Topics cover Expressing analysis and design models using the UML, a standard diagramming notation, Applying patterns to assign responsibilities and design collaborations and more. DLC: Object-oriented methods.
Nguyên lý xây dựng phần mềm
Keywords: Object-oriented methods (computer science),Uml (computer science),System analysis,System design